Analyzing the Financial Position of the Greek Audit Firms - Gerasimos Rompotis (Journal of Accounting and Management Information Systems (JAMIS), 2025)
Research Question: What was the financial position of the twenty largest Greek audit firms during the period 2015-2023? Motivation- There is just one study that examines the financial position of the Greek audit companies. However, this study does not assess the factors that can affect the financial performance of the audit firms operating in Greece, nor does it discriminate between Big 6 and non-Big 6 firms. Given the significance of the Greek market in the region, a study on the local audit companies is highly appreciated. This is the gap in the literature that the current study aims to fill. Idea: Along with analyzing the financial position of the Greek audit companies, also focusing on the impact of the recent Greek sovereign crisis and the possible of Covid-19 on revenue and financial performance, we explore the factors that can affect financial performance, including audit firms' status, size, age, leverage, liquidity, and efficiency. Data: We gather the financial statements of the twenty largest Greek audit firms during the period 2015-2023. Tools: First, we examine the main financial figures of the Greek auditing firms. Then, we focus on the structure of their balance sheet. Next, we calculate key financial ratios. Last, we attempt to identify the factors that may affect the financial performance of audit firms through econometric analysis, as well as how these factors affect performance. Findings: Our findings indicate that the Greek audit firms have sound liquidity but are largely financed by foreign capital rather than equity. At the same time, their ability to exploit their assets to make revenue is very strong. By comparing the Big 6 to other companies, it has been found that the smaller firms are in a better relative financial position than the Big 6. Moreover, it is shown that sales, profitability, and financial performance have been significantly larger after the end of the Greek financial crisis in 2019 than they were during the crisis (i.e., 2015-2019). On the other hand, the Covid-19 health crisis did not have any impact on financial performance. Finally, a significantly negative correlation is found between companies' age and financial performance. This is also the case about efficiency. Debt-to-equity and cash ratios are positively related to financial performance. The relationship between the acid-test ratio and performance is significant, too, although not unequivocal. Contribution: This is the first study to examine the factors that may affect the financial performance of the Greek audit firms, as well as the possible impact on financial performance of the Covid-19 health crisis. Given the significant role of Greece as a peripheral power, our results could be reflected in other countries with similar economic characteristics and comparable audit markets. From a practical point of view, the current study provides useful insights into some of the factors that may affect the financial performance of audit firms so that the latter elaborate on these factors to further enhance their performance.
Keywords: M42; 650; Audit Firms; Financial Performance; Liquidity; Leverage; Profitability; Efficiency